Solvent mixtures, preliminary remarks [Air Monitoring Methods, 2014]. Issue 3 (25th July 2016) - Tschickardt, M.; Krämer, W.; Breuer, D.; Eisenhardt, A.; Karmann, J.; Moritz, A.; Nitz, G.; Schmitt, R.; Schneider, W.; Hebisch, R.; Hartwig, A.; ,
Abstract : The preliminary remarks describe the updated versions of the six solvent mixture methods published in 1998 in this collection. The revised methods describe the determination of solvents in the workplace air by means of adsorption onto solid adsorbents followed by gas chromatographic analysis, whereby active sampling is performed. Chloroorganic solvents as well as benzene are no longer taken into consideration. Sampling is performed by drawing air through an adsorbent tube using a suitable flow‐regulated pump. In addition to the choice of adsorbent, the individual methods that cover the different components of the solvent spectrum differ in the manner of sample preparation and the analytical measuring principle. The preliminary remarks contain a table with numerous widely used solvents (including its characteristics and physical parameters) that can be determined with the revised methods. Furthermore, the concentration range of an individual solvent component is designed in such a way that its Occupational Exposure Limit (OEL) can be monitored at workplaces. The performances of comparative tests are described and the measurement results of the analysis are presented.